How Business Incubators Foster Idea Development and Business Plans: A Case Study of Montenegro - Lacmanović, Darko; Raspor, Andrej; Lacmanović, Jelena (Improving Entrepreneurial Journey, 2025)
The research includes 15 potential entrepreneurs from Montenegro who attended training in a business incubator and who evaluated the mentoring process. Participants agreed that the success of a business requires a lot of work hours (Average 5.00), which supports the Entrepreneurial Commitment Theory. Enjoyment of problem-solving (Mean 4.83) reflects the Theory of Problem Solving in Entrepreneurship. They were the least likely to agree that they think best under pressure (Mean 3.80), which is consistent with the Yerkes-Dodson law. High scores were given for the ability to delegate, interest in work, and self-confidence (Average 4.57-4.51), consistent with the Self-Efficacy Theory. Task prioritization, leadership motivation, and readiness to face problems were also rated well (Average 4.43-4.40). Activities such as problem-solving, market research, financial planning, marketing strategies, and networking received the highest scores (Average 5.00). Mentors received high grades for understanding business ideas and offering support (Average 4.66). The participants rated the entire mentoring experience very positively (Average 4.57), whereby the mentors contributed to the personal and entrepreneurial development of the participants. The research emphasizes that a high level of commitment, effective problem-solving, adequate support from mentors, and practical experience are key to the success of entrepreneurs.